Exploring Digital Solutions to Enable End Consumer Participation in Green Energy Adoption - Chaudhary, Prakhar (Digital Repository of Theses - SSBM Geneva, 2025)
Utilities are driving energy transition projects aiming for carbon-free generation and promoting green energy initiatives globally. To achieve these goals, utilities must have a socioeconomic perspective and a multifaceted strategy involving stakeholders like investors, customers, competitors, and regulatory agencies. Active customer involvement can help develop innovative plans to reduce carbon footprint. However, there are limited options available for involving customers in these efforts. This research study enables us to comprehend why it is very crucial to enhance end-consumer participation in the net zero target globally. The study employed a mixed-method approach, combining statistical analysis of quantitative data with qualitative insights to provide a well-rounded evaluation. It analysed the key dimensions, including technological, economic, social, environmental, and institutional support. The key areas that were considered are residential, EV charging parking lots, commercial (malls/offices), industrial, and emergency backup systems. The data analysis for this study was done, using SPSS (Statistical Packages for Social Sciences) Software. The research found that through the implementation of Power Bank on Cloud (PBoC) systems, there are notable enhancements in energy management procedures in aspects of operation overheads, costs, and environmental effects. They show high compatibility with the already implemented systems and represent an improvement in energy reliability in emergency cases. From an economic point of view, PBoC systems allow efficient use of energy thus enhancing energy loss in cases of power outages. Environmentally, they foster sustainability by reducing the emission of carbon by energy operations. The study also examines institutional alignment; it asserts that PBoC systems meet energy management standards and regulations sufficiently. The study finds out that the systems of PBoC have the ability to transform energy management in different sections of organizations to meet the pressing needs of the future including energy wastage and deterioration of the environment. Recommendations include enhancing technological Innovation, promoting policies that will support this process and engagement of key stakeholders to increase the level of adoption and utility.